Kajian Psikologi Tentang â€œBelajarâ€ Dalam Al-Qurâ€™an/Hadis - Imam Hanafi (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2017)
Learning is a process taken by a person in order to get the knowledge. Science itself in Islam has a very urgent position because it will be able to deliver people to the perfection of life in the world, especially in the hereafter. In the Qur'an there are many verses that show about learning, learning principles, etc. Therefore, the